Austria, Hungary, and the Habsburgs : essays on Central Europe, c.1683-1867 - Evans, R. J. W. (Robert John Weston), 1943- (OUP E-Books., 2006)
These elegantly written essays by the leading historian of the Austro-Hungarian empire explore the political and religious history of the Habsburg lands, Europe's only true multinational state. They illuminate key aspects of the evolution towards modern statehood and national awareness in Central Europe over more than two centuries of cultural and social transition. - ;This book address a number of interrelated themes over two hundred years and more in the political, religious, cultural, and social history of a broad but often neglected swathe of the European continent. It seeks - against the.